Abstractions and aesthetic representations of loss in film - Choo, Austen Jin Ting (2018)
This paper aims to explore the aesthetic representations of death and loss in film through film theories and concepts like Schrader’s (1972) transcendental style and it’s application in the thesis film Kintsugi. Alongside comparisons to Kore-eda’s debut feature Maborosi, the visual language of loss will be examined through a discourse on the ideas of cinematic stasis and its patterns alongside time and montage, to establish how these filmic devices are utilised to portray themes of finality and bereavement. By investigating the aesthetic treatment towards filmic representations of human finitude, this paper further seeks to establish how the relationship between the style of a film, and its thematic narrative, is rooted in the nature of cinema itself. This paper concludes that the abstract depictions of death in film is a standpoint from which audiences view life, through the functionalities of cinema itself as well as its artistic measures. Ultimately, the paper raises questions on the filmic construct of human behaviour and emotions amid such instances of death, expounding on how the “transcendent” is able to be represented within films through a cross-pollination of ideas in elements like semiotics, structuralism and its relationship with auteurism, allowing for future dialogue and conversations towards abstract depictions and representations of life and death to be examined within the malleable and ever-expanding nature of film and filmmaking.